Athletes evaluation of training loads with different fitness levels in women`s handball - Oytun, M.; Açikada, C.; Hazir, T.; Tinazci, C. (International Journal of Applied Exercise Physiology, 2020)
Establishing a training load (TL) for athletes is a major problem. Session rating of perceived exertion (sRPE) is one way of establishing the TL while fitness levels of the athletes may influence the perception of a TL. The aim of this study was, first, to determine the coaches` training load and athletes` perception of the same load, and, second, if there was a difference in fitness levels of athletes reflected in the arbitrary points, by using sRPE. A total of 60 women players playing in the first division women`s handball league in North Cyprus took part in the study. They were divided into upper, middle, and lower fitness groups according to their test results in endurance, jumping, speed, agility, and anaerobic fitness tests. The training load (TL) was determined by multiplying the sRPE by the time taken for the session and the resulting value was expressed in arbitrary points. 57 total training sessions were analyzed and the difference between the fitness groups was tested by ANOVA. There was a significant difference between the athletes and coaches arbitrary points 695.5?229.7 and 814.3± 282.0, respectively (t = 2.47, p<0.02). In general, with the coaches` TL arbitrary points with the upper group absolute peak power (PP) (r = -0.562; p = 0.029) and lower group counter movement jump (CMJ) (r = 0.548; p = 0.028) had a high and significant correlation, while the data from the rest of the players` middle fitness groups did not have any significant correlations. The coaches` TL decisions were made irrespective of the athletes` fitness levelsandconsidered having the same fitness and received the same training schedules.